Landslides and their mitigation in Gangtok, Sikkim - Larsen, Jan Otto; Grimstad, Eystein; Bhasin, Rajinder; Dhawan, Ashok K.; Singh, Rajbal; Verma, S. K. (Journal of Nepal Geological Society, 2000)
A study of landslides was carried out around Gangtok, the capital city of Sikkim. Apart from a general survey of the area, detailed investigations were made at Chanmari and Tathangchen as well as along the National Highway 31A. Among various landslides, rockslides predominate and they fail mainly along the foliation planes dipping parallel to the hillside. For example, the Burdang Landslide and Tathangchen Landslide are basically rockslides on schist or phyllite. To monitor the ground movement at the Chanmari Landslide, six control points were set along the existing drainage channel. The movement of the points is recorded twice a month. Also, four piezometers are se t above the landslide scarp to measure the pore water pressure. A similar system with four control points and two piezometers is also established along the main road at the Chanmari Village. As rainfall is the main triggering factor, control of surface and subsurface runoff is the most important protection measure. The recommended mitigation measures include the construction of drains and retaining walls. It is also recommended to enforce the Government Building Regulations in the landslide-prone areas.